2006
DOI: 10.1521/aeap.2006.18.supp.137
|View full text |Cite
|
Sign up to set email alerts
|

Adapting the Popular Opinion Leader Intervention for Latino Young Migrant Men Who Have Sex With Men

Abstract: Young Latino migrantmen who have sex with men are at high risk for HIV infection. The Popular Opinion Leader intervention, shown to be effective with White gay men, was adapted by the Farmworker Justice Fund, Inc., for this Latino migrant population. This project, called the Young Latino Promotores, was implemented over a 2-year period by community-based organizations in Vista, California, and McAllen, Texas, with capacity building assistance from the Farmworker Justice Fund, Inc. We report on challenges, prel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(82 citation statements)
references
References 10 publications
1
81
0
Order By: Relevance
“…Culturally specific educational interventions that incorporate these behavioral strategies but also promote empowerment and address social contexts and pressing concerns such as housing and employment have been shown to be effective for HIV-risk reduction and improved quality of life among African American drug-using women (Wechsberg, Lam, Zule, & Bobashev, 2004). Further, interventions that mobilize community networks around HIV as well as provide small group and individual educational and skills-building interventions supported by specifically developed, culturally tailored audiovisual materials (such as radio shows, comic books, and "role model stories") have been shown to be effective for reducing HIV risk behavior among African American women and Latinas, Thai migrant female factory workers, and male Mexican migrants (Cash, Anasuchatkul, & Busayawong, 1994;King et al, 2008;Mishra, Sanudo, & Conner, 2004;Sommerville, Diaz, Davis, Coleman, & Taveras, 2006). Depending on the cultural context, couple-based risk reduction strategies such as negotiated safety and improving conflict resolution skills or framing the condom broadly as a tool for promoting family health rather than narrowly as an HIV-prevention intervention may be appropriate (Bhattacharya, 2004;Riehman, Wechsberg, Francis, Moore, & Morgan-López, 2006).…”
Section: Downloaded By [University North Carolina -Chapel Hill] At 07mentioning
confidence: 99%
“…Culturally specific educational interventions that incorporate these behavioral strategies but also promote empowerment and address social contexts and pressing concerns such as housing and employment have been shown to be effective for HIV-risk reduction and improved quality of life among African American drug-using women (Wechsberg, Lam, Zule, & Bobashev, 2004). Further, interventions that mobilize community networks around HIV as well as provide small group and individual educational and skills-building interventions supported by specifically developed, culturally tailored audiovisual materials (such as radio shows, comic books, and "role model stories") have been shown to be effective for reducing HIV risk behavior among African American women and Latinas, Thai migrant female factory workers, and male Mexican migrants (Cash, Anasuchatkul, & Busayawong, 1994;King et al, 2008;Mishra, Sanudo, & Conner, 2004;Sommerville, Diaz, Davis, Coleman, & Taveras, 2006). Depending on the cultural context, couple-based risk reduction strategies such as negotiated safety and improving conflict resolution skills or framing the condom broadly as a tool for promoting family health rather than narrowly as an HIV-prevention intervention may be appropriate (Bhattacharya, 2004;Riehman, Wechsberg, Francis, Moore, & Morgan-López, 2006).…”
Section: Downloaded By [University North Carolina -Chapel Hill] At 07mentioning
confidence: 99%
“…Thirty-eight (50 %) interventions included condom use skills training, while the remaining half relied on 23 or social network-based strategies 24 to disseminate prevention messages.…”
Section: Intervention Delivery Methodsmentioning
confidence: 99%
“…Serial surveys of community members over two years demonstrated an increase in the proportion of protected anal intercourse. 24 However, other interventions were simultaneously implemented in the community and the observed increase in protected sexual intercourse cannot be attributed to this intervention alone.…”
Section: High-risk Menmentioning
confidence: 99%
“…Taken together, these interventions, which consisted of either counseling sessions and/or group educational sessions, were found effective in increasing condom use and decreasing risky sexual behaviors. Furthermore, two studies targeting Latino men [18,19] were found effective in decreasing risky sexual behaviours through their educational interventions as was a peer-led educational and HIV testing study conducted in a Chinese setting [20]. In addition, four more prevention interventions studies were found effective in decreasing risky sexual behaviours through behavioural, cognitive, individual and/or group counseling sessions [8,[21][22][23].…”
Section: Community-based Interventionsmentioning
confidence: 99%